2018
DOI: 10.18632/oncotarget.25962
|View full text |Cite
|
Sign up to set email alerts
|

Race and nodal disease status are prognostic factors in patients with stage IVB cervical cancer

Abstract: BackgroundPatients presenting with stage IVB cervical cancer pose a significant clinical challenge. While previous studies described several poor prognostic factors, they were limited by small sample sizes. The aim of this study was to identify clinicopathological prognostic factors in a large sample of patients with stage IVB cervical cancer at a single institution.MethodsPatients with primary stage IVB cervical cancer diagnosed between 1992 and 2011 were extracted from a search of the MD Anderson Cancer Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…Nishio et al [36] stated that racial differences in cervical cancer incidence and death rates were indisputable, consistent with our findings showing that racial differences affected patients' OS. However, the reasons for racial differences in mortality rates remain unclear and controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Nishio et al [36] stated that racial differences in cervical cancer incidence and death rates were indisputable, consistent with our findings showing that racial differences affected patients' OS. However, the reasons for racial differences in mortality rates remain unclear and controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Stage IIIC1 cervical cancer is not a single disease entity, and local tumor factors remain the primary determinant of survival. Nishio et al [6] showed that the prognosis of women with cervical cancer with extra-pelvic metastasis varies based on metastatic sites outside of the pelvis. Specifically, outcomes for metastatic cervical cancer solely in the para-aortic LNs are superior when compared to cervical cancer metastasized to other extra-pelvic sites.…”
Section: Gynecologic Oncologists' Perspectives: For Whom This Platformentioning
confidence: 99%
“…Patients who develop distant metastases are rarely curable. The 5-year survival of stage IVB patients is poor and approximately 50% of these patients show a fatal outcome within 1 year [345].…”
Section: Introductionmentioning
confidence: 99%